Answer:
420,000
Step-by-step explanation:
If 140,000 is
of what she had yesterday, then you just multiply the number by 3 because
times 3 is
, which is 1.
Answer:
x = 4
y = 3
Step-by-step explanation:
x = 10 - 2 y
substitute x = 10 - 2y into 2x - y = 5
20- 5y = 5
then
y = 3
and
x = 4
Mark brainliest
Since the angle is positive, you can find any coterminal angle by applying:
Angle + x = 2π ==> 7π/6 + x = 2π ==> x = 2π - 7π/6
x= 12π/6 -7π/6 = 5π/6
So the angle 5π/6 is the coterminal of 7π/6
The midpoint bisects PR, making it 2 equal halves.
Answer:
![\displaystyle \sf h( - 1) = - \frac{ 2}{3}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%5Csf%20h%28%20-%201%29%20%3D%20%20%20-%20%5Cfrac%7B%20%20%20%202%7D%7B3%7D%20)
Step-by-step explanation:
we are given a function
![\displaystyle \sf h(x) = \frac{2x - 6}{4 {x}^{2} + 8}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Csf%20h%28x%29%20%3D%20%20%5Cfrac%7B2x%20-%206%7D%7B4%20%7Bx%7D%5E%7B2%7D%20%20%2B%208%7D%20)
we would like to simplify it for h(-1)
in order to do so
substitute the value of x
![\displaystyle \sf h( - 1) = \frac{2 \cdot - 1- 6}{4 { (- 1)}^{2} + 8}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Csf%20h%28%20-%201%29%20%3D%20%20%5Cfrac%7B2%20%5Ccdot%20-%201-%206%7D%7B4%20%7B%20%28-%201%29%7D%5E%7B2%7D%20%20%2B%208%7D%20)
by order of PEMDAS
simplify square:
![\displaystyle \sf h( - 1) = \frac{2 \cdot - 1- 6}{4 { ( 1)}^{} + 8}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Csf%20h%28%20-%201%29%20%3D%20%20%5Cfrac%7B2%20%5Ccdot%20-%201-%206%7D%7B4%20%7B%20%28%201%29%7D%5E%7B%7D%20%20%2B%208%7D%20)
simplify multiplication:
![\displaystyle \sf h( - 1) = \frac{ - 2 - 6}{4 { }^{} + 8}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Csf%20h%28%20-%201%29%20%3D%20%20%5Cfrac%7B%20-%202%20-%206%7D%7B4%20%7B%20%7D%5E%7B%7D%20%20%2B%208%7D%20)
simplify addition:
![\displaystyle \sf h( - 1) = \frac{ - 2 - 6}{12}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Csf%20h%28%20-%201%29%20%3D%20%20%5Cfrac%7B%20-%202%20-%206%7D%7B12%7D%20)
simplify subtraction:
![\displaystyle \sf h( - 1) = \frac{ - 8}{12}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Csf%20h%28%20-%201%29%20%3D%20%20%5Cfrac%7B%20%20%20-%208%7D%7B12%7D%20)
reduce fraction:
![\displaystyle \sf h( - 1) = - \frac{ 2}{3}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20%5Csf%20h%28%20-%201%29%20%3D%20%20%20-%20%5Cfrac%7B%20%20%20%202%7D%7B3%7D%20)